051 Injuries are negatively associated with team performance in professional cricket. (3rd March 2020) - Goggins, Luke; Peirce, Nicholas; Griffin, Steve; Langley, Ben; Stokes, Keith; McKay, Carly; Williams, Sean
Abstract : Background: A negative association between injuries and team success has been demonstrated across a number of sports, but the nature of this association in professional cricket teams is currently unclear. Objective: To examine the relationship between injuries and team success in professional cricket. Design: A retrospective analysis of all match time-loss injuries and County Championship point tallies for nine seasons (from 2010 – 2018 inclusive). Setting: Eighteen First-Class County Cricket (FCCC) cricket teams in England and Wales. Patients (or Participants): Professional male senior first-team cricketers registered to one of the eighteen clubs (mean n=507 players/season). Interventions (or assessment of risk factors): Two injury measures were assessed for within-team (linear mixed model) and between-team (correlation) effects; match time-loss injury incidence and burden, to account for both the frequency and severity (days lost from competition and practice) of injuries. Main outcome measurements: County Championship league points tally was used as the measure of team success. Results: A moderate negative correlation was found between injury burden and team performance (r=-0.36; 90% CI: -0.7 to 0.1; likely negative ). A reduction in match injury incidence of two match time-loss injuries per 1, 000 days of play within a team (90% CI 1.4 to 3.0; possibly negative ), or a reduction in match injury burden of 74 days per 1, 000 days of play (90% CI 50.2 to 109.0; possibly negative ) in any given season was associated with the smallest worthwhile change in County Championship points (+13 points) for Division 1, but not for Division 2. Conclusions: Moderate reductions in injury burden potentially have worthwhile effects on performance for a domestic cricket team in the County Championship Division 1.